Pengaruh Pola Asuh Otoriter Orang Tua Dan Regulasi Emosi Terhadap Sibling Rivalry Pada Remaja Di Kecamatan Tebet. - Meielsa Dewi, Nindi; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study is a quantitative research aimed at examining the influence of authoritarian parenting styles and emotional regulation on Sibling Rivalry among adolescents in the Tebet sub - district. The sampling technique employed is accidental sampling. The participants in this study comprised 100 respondents, a result obtained from the Slovin formula calculation. Data collection in this research utilized three scales: the Sibling Rivalry scale, the Authoritarian Parenting scale, and the Emotional Regulation scale. The Sibling Rivalry scale consists of 17 items with item discrimination values ranging from 0.303 to 0.588 and a reliability coefficient of 0.639. The data were analyzed using Simple Linear Regression and Multiple Linear Regression methods via JASP 0.18.33.0 for Windows. The results indicate that: 1) There is an influence of authoritarian parenting on Sibling Rivalry (r = 0.208 and p < 0.05); 2) There is an influence of emotional regulation on Sibling Rivalry (r = 0.364 and p < 0.05); 3) The combined effect of authoritarian parenting and emotional regulation on Sibling Rivalry is not significant (r = 0.371 and p > 0.05), indicating that there is no effect of authoritarian parenting and emotional regulation on Sibling Rivalry among adolescents in the Tebet sub-district